Pendampingan Pengelolaan Keuangan Berbasis Teknologi Pada Badan Usaha Milik Desa (BUMDES) Citra Permai - Rodiah, Siti; Azhari, Intan Putri; Suci, Rama Gita; Marlina, Evi; Azmi, Zul; Putri, Adriyanti Agustina; Armel, R. Septian (Jurnal Pengabdian UntukMu NegeRI, 2023)
BUMDesa is a business run by the Village based on the Village Deliberation and has the aim of improving the village economy. BUMDesa management cannot be separated from the preparation of financial reports. BUMDesa Citra Permai has experienced a change in membership and the addition of products and services in its economic activities so it requires assistance in BUMDesa management, especially in the preparation of financial reports. The UMRI Accounting Study Program Community Service Team provides training and assistance in preparing financial reports using the Excel For Accounting (EFA) application. Training on preparing financial reports using EFA was attended by all Citra Permai BUMDesa managers. This activity was carried out for 3 days using four methods including surveys, input/account addition, implementation and evaluation. During the implementation of the community service activities, BUMDesa managers seemed enthusiastic by providing various questions regarding transactions that might occur and how BUMDesa recognizes and records these transactions in EFA. After simulating the use of EFA, managers know the benefits and convenience of using EFA.